PEMETAAN PARTISIPATIF DI TANAH ADAT (Studi Kasus Tanah Ulayat Nagari Bidar Alam Kabupaten Solok Selatan) - Putra, Randu Prayoga; Yulfa, Arie (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
This research aims to. 1) conduct participatory mapping of customary land in Nagari Bidar Alam. 2) classifying Bidar Alam's customary land use. This type of research is a combination of qualitative and quantitative research. Primary data was obtained from FGD with the Bidar Alam community. The tracking data is processed using arcGIS 10.3. The results of this study are: 1) The customary land in Nagari Bidar Alam has an area of ​​100.84 Ha. Which consists of 4 tribes, namely the Kampai tribe covering an area of ​​43.23 hectares, Malays covering an area of ​​33.75 hectares, Kuti Anyir covering an area of ​​6.18 hectares, and Tigo Lareh covering an area of ​​17.66 hectares. 2) The results of the classification of land use on customary lands consist of plantations with an area of ​​99.99 ha with a percentage of 99.18% which is dominated by oil palm plantations. Settlements have an area of ​​0.03 ha which are located in the ulayat of the Malays with a percentage of 0.01%. Meanwhile, Semak Scrub is spread among the Kampai, Malay, and Kuti Anyir tribes and has an area of ​​0.08 ha with a percentage of 0.79%.